Virtue and Proper Use in Plato’s Euthydemus and Stoicism - Dentsoras, Dimitrios (Peitho. Examina Antiqua, 2019)
The essay examines the description of virtue as a craft that governs the proper use of possessions in Plato’s Euthydemus and Stoicism. In the first part, I discuss Socrates’ parallel between wisdom and the crafts in the Euthydemus, and the resulting argument concerning the value of external and bodily possessions. I then offer some objections, showing how Socrates’ craft analogy allows one to think of possessions as (qualifiedly) good and ultimately fails to offer a defense of virtue’s sufficiency for happiness. In the second part, I examine the Stoics’ craft analogy and note a number of differences from Socrates’ account in the Euthydemus. These include the Stoic claim that external advantages never make any contribution to happiness, even when properly used, and the claim that, unlike other crafts, wisdom does not require any external possessions in order to be exercised and yield benefit and happiness. I then place these differences against the backdrop of the debate regarding virtue’s sufficiency for happiness and argue that the Stoic craft model of virtue fares better than its Socratic antecedent.